REFORMASI PENDIDlKAN MENUJU MASA DEPAN PEMBANGUNAN BANGSA - Rosidah, Rosidah (Jurnal Cakrawala Pendidikan, 2005)
Global era is a challenge for seizing competitive quality among nations. The challenge become an agenda for realizing an education system able to answer some requirement for development. Education is the main pillar of development Actually, functional decadence of education h curred within erosion in the process of striking objecti ve of education’: Reformation is urgent, in terms of eduction system, the learning of education personal, the existence education personals. Reformation in the three elements should be synergic and progressing mission/visions for education leading to the purpose of human development, generating human who are intellegent, piety, scholarly, humanisstic, adabtive, indenpendent, moralized, fair, and populism. Somes effort for realizing the objecti ves are the responsibility of goverment, schools and society. Thought this writing, it is discussed some issues of education reformations by converting aspects of institutions, profesionalism of education personals, and their relation to the future of nation development.